Technologies applied in the monitoring and control of the temperature in the Cold Chain (2018)
In this article, an analysis of the technologies applied for the monitoring and control of the temperature of perishable products in the cold chain is presented. Also, a general description of the stages of the process is made from the production, transport, storage, distribution, points of sale and final consumer. The objective of this work is to identify the current technologies trends that can be implemented in a comprehensive way in a cold chain that allow to save costs, significant time and reduce the waste of food in companies. In addition, there is a brief discussion of future work that can be implemented to ensure the quality and safety of food and medicines throughout the cold chain.